Students’ Perspective on English Pragmatic Based Material for Students of Hotel Management Study Program - Rahman, Benni Ichsanda; Husnaini, Husnaini (Association of Language Teachers in Southeast Asia (ALTSA), 2019)
Understanding someone’s utterances who has different cultural background with the listener certainly should be intended. Lot of miscommunications occurred between speakers and listeners, in case that the listener does not get the core intent meaning of the speaker. Specifically, what has been conveyed implies indirect meaning. Thus, Understanding pragmatic is very important. Rahman (2017) has created a book with pragmatic approachment. Rahman (2017) carries various daily hotel conversations that convey pragmatic meaning. Then, the book has been taught to the students as well. Thus, this study is aimed to investigate the students’ perspective on that book implementation. A Survey was used to collect the data by using questionnaire and interview. 40 students of hotel management were involved in this study. The research reveals that 33 respondents (82.5%) strongly agree that the book is contextual with their daily work and practice. It is also revealed the fact that 34 respondents (85%) said the book represents their hard skill levels. Yet, the book also motivates students to learn by seeing the data that 31 (78.5%) students informed that they are curious to learn the book by practice.